Validation as a Binding Condition of Operative Reality: Institutional Admissibility in Social Ontology - Aung, Ye Si Thu (Jayapangus Press, 2026)
Institutional systems repeatedly generate a structural divergence between intrinsic adequacy and institutional operability. Entities possessing coherent structure, competence, or evidential support frequently remain unable to circulate within organized domains, while other entities continue to generate authoritative consequences despite contested intrinsic adequacy. This asymmetry indicates that institutional operability is not governed by epistemic truth, causal capability, or intrinsic properties alone. The operative condition lies in admission. Within institutional systems capable of enforceable recognition, entities become effective only after passing the admission threshold that authorizes participation in the domain’s decision structure. The present analysis develops a social-ontological model specifying validation as the binding condition of institutional admissibility. The investigation proceeds through analytical reconstruction of institutional mechanisms combined with comparative conceptual illustration across three structurally distinct domains: monetary circulation, professional jurisdiction, and scientific publication. These domains isolate the distinction between intrinsic reality, defined as the material, semantic, or causal constitution of entities, and operative reality, defined as the authorization under which entities may function within institutional systems regulating participation, responsibility, and circulation. The analysis establishes that institutional systems stabilize action through validation regimes governing admissibility rather than through direct evaluation of intrinsic adequacy. Validation admits entities into the domain’s operative field and thereby permits circulation, authority, and responsibility allocation. Withdrawal of validation produces immediate institutional inoperability while intrinsic properties remain unchanged. This discontinuity shows that institutional efficacy depends on admission status rather than intrinsic capability, establishing operative reality through validation within social systems.